Knowledge, attitudes and practices of men in a South African rural community in relation to exclusive breastfeeding - Oscar M. Mabele; Matthew O.A. Benedict; Wilhelm J. Steinberg; Elizabeth Reji; Cornel van Rooyen; Anthonio O. Adefuye (South African Family Practice)
Background: Several lifelong maternal, child and societal health benefits have been associated with exclusive breastfeeding (EBF). However, despite all the potential advantages, EBF rates have been consistently low in developing countries, including South Africa. It has been suggested that the knowledge, attitudes and practices of male partners in relation to EBF are amongst the important factors that contribute to the success of EBF practices. Hence, the aim of this study was to determine the knowledge, attitudes and practices of men in Botshabelo, Free State province, South Africa, regarding EBF.